Aluminum-zinc-silicon-magnesium coated steel plate with excellent bending property and manufacturing method of aluminum-zinc-silicon-magnesium coated steel plate

By adjusting the plating alloy phase and adding titanium and rare earth elements, combined with cooling process control, the problem of cracking of aluminum-zinc silicon-magnesium-coated steel plate during the molding process is solved, and excellent bending performance and high corrosion resistance are achieved. It is suitable for engineering construction color Paint the board.

CN119121101AActive Publication Date: 2024-12-13МААНЬШАНЬ АЙРОН ЭНД СТИЛ КО ЛТД
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411166308.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-23
Publication Date
2024-12-13
Estimated Expiration
2044-08-23

AI Technical Summary

Technical Problem

Aluminum-zinc silicon-magnesium-coated steel plates are prone to cracking during the molding process, resulting in poor molding performance and unable to meet market demand.

Method used

By adjusting the shape and proportion of the alloy phase in the plating layer, reducing the aluminum flower size on the surface of the plating layer, controlling the size of the magnesium-zinc phase and silicon phase, adding titanium and rare earth elements to refine the grains, and combining with the cooling process control, it forms an excellent bending performance Aluminum zinc silicon magnesium coating steel plate.

Benefits of technology

It significantly reduces the incidence of plating cracks, improves the bending deformation performance of the plating, and maintains high corrosion resistance, and is suitable for the field of color-coated plates in engineering construction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121101A_ABST
    Figure CN119121101A_ABST
Patent Text Reader

Abstract

The invention provides an aluminum-zinc-silicon-magnesium coated steel plate with excellent bending property and a manufacturing method of the aluminum-zinc-silicon-magnesium coated steel plate. A plating solution comprises the following components in percentage by mass: 45%-50% of Zn, 1.5%-2.5% of Mg, 1.0%-1.5% of Si, 0.002%-0.005% of Ti, 0.04%-0.06% of La + Ce and the balance of Al and inevitable impurity elements. Compared with the prior art, by controlling the content of a magnesium-silicon alloy phase in a plating layer, controlling the sizes of a magnesium-zinc phase, a zinc-rich phase and a silicon phase, and adding a proper amount of titanium and mixed rare earth elements to refine grains, the wettability of a plating solution is improved, and a cooling process control strategy is implemented in a matched manner; therefore, the aluminum-zinc-silicon-magnesium coated steel plate with excellent bending deformation performance is obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of metallurgical technology, specifically the field of steel-based hot-dip plating, and specifically relates to an aluminum-zinc-silicon-magnesium coated steel plate with excellent bending performance and a manufacturing method thereof. Background Art

[0002] Hot-dip coating is of great significance for protecting steel plates, improving their durability and reducing costs. In order to improve the corrosion resistance of traditional hot-dip galvanized steel plates and save zinc resources, aluminum is added to the pure zinc coating. At the same time, a certain amount of silicon is added to inhibit the violent reaction between aluminum and steel base to form an aluminum-zinc-silicon coating with better corrosion resistance.

[0003] With the growing demand for high corrosion resistance and high formability of steel plates in specific environments such as construction and animal husbandry or long-term corrosive media environments in recent years, the aluminum-zinc-silicon-magnesium coating with excellent corrosion resistance is formed by adding magnesium elements to the aluminum-zinc-silicon coating. It is considered to be the next generation of protective coating materials with good development prospects at present, and has very broad development prospects in the field of engineering and construction color-coated plates.

[0004] The application scenarios of aluminum-zinc-silicon-magnesium coated steel sheets require that they have high corrosion resistance and certain forming properties. However, since aluminum-zinc-silicon-magnesium coatings belong to aluminum-based multi-element alloy coatings, the coating forms an organizational structure with aluminum dendrites as the structural skeleton and alloy phases and eutectic phases between dendrites as fillings during the solidification process. The inhomogeneity of the coating organization makes the coating prone to cracking during the forming process. Compared with pure zinc and low aluminum content zinc-aluminum-magnesium coatings, its forming properties are poor, which to a certain extent restricts the application of aluminum-zinc-silicon-magnesium coated steel sheets and their color-coated sheets in the market.

[0005] The patent with the publication number CN 101910444 A published on December 8, 2010 discloses a metal-coated steel strip, wherein the Al-Zn-Si-Mg alloy-coated strip is disclosed, wherein the Al-Zn-Si-Mg alloy comprises the elements aluminum, zinc, silicon and magnesium in the following weight percentage ranges: aluminum: 40-60%, zinc: 40-60%, silicon: 0.3-3%, and magnesium: 0.3-10%. The coating has Mg2Si particles in its microstructure. The distribution of the Mg2Si particles is such that only a small portion of the Mg2Si particles or at least substantially no Mg2Si particles are present in the coating surface area, but its forming performance cannot meet current use requirements. Summary of the invention

[0006] The object of the present invention is to provide an aluminum-zinc-silicon-magnesium coated steel plate with excellent bending properties and a method for manufacturing the same, by adjusting the morphology and proportion of the alloy phase in the coating, the crack incidence rate is reduced; by reducing the size of the aluminum flower on the surface of the coating, the extension and expansion behavior of the cracks in the coating is inhibited, and the proportion of long cracks after the coating is bent and deformed is reduced, so that it meets the corrosion resistance and has better forming performance.

[0007] The specific technical solutions of the present invention are as follows:

[0008] An aluminum-zinc-silicon-magnesium coated steel plate with excellent bending performance comprises a substrate, an inhibition layer and a coating layer.

[0009] In the cross-sectional organizational structure of the aluminum-zinc-silicon-magnesium coated steel sheet with excellent bending performance, the coating thickness deviation measured from the inhibition layer between the coating and the substrate to the coating surface within a 50 μm length randomly selected in the horizontal direction is no more than 10%. The calculation method is: the coating cross-sectional organizational structure is under a microscope magnification of 200 times, within a 50 μm length randomly selected in the horizontal direction, |thickest coating or thinnest coating thickness - theoretical coating thickness| / theoretical coating thickness×100%, and the coating theoretical thickness calculation method is: single-sided coating weight / coating density.

[0010] The cross-sectional microstructure of the coating has at least 3 layers of coating structures divided by aluminum interdendritic alloy phase (Mg-Si or Mg-Zn phase) or eutectic structure in a direction perpendicular to the coating thickness;

[0011] The mass content of the Mg-Si phase contained between the dendrites in the cross-sectional microstructure of the coating is more than 3 times the mass content of the silicon phase between the dendrites;

[0012] The distance between the single Si phase distributed between the dendrites in the cross-sectional microstructure of the coating and the inhibition layer between the coating and the substrate in the direction perpendicular to the coating thickness is no more than 1 / 3 of the total coating thickness, and the mass content of the single Si phase accounts for no more than 1% of the interdendritic phase;

[0013] The cross-sectional microstructure of the coating contains Mg-Zn phases between dendrites in irregular block distribution and a size of no more than 3 μm;

[0014] The zinc-rich phase between dendrites in the cross-sectional organizational structure of the coating is distributed in granular or irregular blocks and has a size of no more than 2 μm.

[0015] The present invention provides a method for manufacturing an aluminum-zinc-silicon-magnesium coated steel plate with excellent bending performance, comprising immersion plating;

[0016] The plating solution used for immersion plating includes the following mass percentage components: Zn: 45% to 50%, Mg: 1.5% to 2.5%, Si: 1.0 to 1.5%, Ti: 0.002% to 0.005%, La+Ce content 0.04% to 0.06%, and the balance is Al and unavoidable impurity elements;

[0017] The content of the inevitable impurity elements is less than 1%.

[0018] The immersion plating control requirements include: the front section fan is used to cool the strip to 440℃ after the air knife is discharged, and the cooling rate is controlled at 8℃ / s~15℃ / s; when the strip temperature is between 390℃≤strip temperature<440℃, the middle section fan is used for cooling, and the cooling rate is controlled at 15~20℃ / s; when the strip temperature is between 280℃≤strip temperature<390℃, the rear section fan is used for cooling, and the cooling rate is controlled at 25~35℃ / s. The fans are all segmented, and the cooling process of the strip is segmented. The corresponding fan cooling is used in a specific temperature range, which is easy to achieve by adjusting the strip running speed and the fan power.

[0019] During the immersion plating process, the zinc pot temperature is 590-600°C, the zinc pot temperature deviation is ±1°C, the strip air outlet knife temperature is 5-10°C lower than the pot temperature, and the cooling device nozzle type is a "straight seam" type.

[0020] The substrate of the aluminum-zinc-silicon-magnesium coated steel sheet with excellent bending performance is a cold-rolled steel sheet;

[0021] The weight of aluminum-zinc-silicon-magnesium coating after immersion plating is 150g / m 2 ~200g / m 2 .

[0022] Compared with the prior art, the present invention controls the contents of magnesium-silicon alloy phase and silicon phase in the coating, controls the size of magnesium-zinc phase and zinc-rich phase, refines the grains by adding appropriate amounts of titanium and mixed rare earth elements, improves the wettability of the plating solution, and implements a cooling process control strategy, thereby obtaining an aluminum-zinc-silicon-magnesium coated steel plate with excellent bending deformation performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is an introduction to the cross-sectional microstructure of the aluminum-zinc-silicon-magnesium coating;

[0024] Figure 2 This is a schematic diagram of the bending deformation force of the aluminum-zinc-magnesium-silicon coated steel plate;

[0025] Figure 3 The cross section and surface morphology of the coating in Example 1;

[0026] Figure 4 This is the bending crack morphology of the coating in Example 1;

[0027] Figure 5 The cross section and surface morphology of the coating of Comparative Example 1;

[0028] Figure 6 This is the bending crack morphology of the coating in Comparative Example 1;

[0029] Figure 7 The photos of the samples of Examples 1 and 2 after 1500 hours of neutral salt spray are shown;

[0030] Figure 8 These are photos of the samples in comparative examples 1 and 2 after 1500 hours of neutral salt spray. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0032] The aluminum-zinc-silicon-magnesium coated steel sheet with excellent bending performance provided by the present invention comprises a substrate, an inhibition layer and a coating; the substrate is sequentially provided with an inhibition layer and a coating, and the coating refers to an aluminum-zinc-silicon-magnesium coating. The microstructure of the aluminum-zinc-silicon-magnesium coating described in the present invention is mainly composed of an aluminum-rich dendrite phase and a zinc-rich phase, a binary alloy phase, and a ternary eutectic phase located between dendrites. Aluminum is the first precipitated phase and grows in a dendrite shape. As the solidification temperature decreases, the alloy phase and the eutectic phase gradually precipitate in the dendrite gaps. The microstructure is as follows: Figure 1 shown.

[0033] The inventors found that the characteristic organizational structure of the aluminum-zinc-silicon-magnesium coating, which uses aluminum dendrites as the structural skeleton and the alloy phase and eutectic phase located between the dendrites as the filling, makes the coating severely segmented and the uniformity of the organization is poor. During the bending process of the coating, the large plastic difference between the aluminum-rich phase and the alloy phase located between the dendrites prevents the coating from deforming uniformly, making the coating prone to cracking. The Zn-rich phase, Mg2Si, MgZn2, Al, and Si single crystals in the coating were selected as the research objects. The inventors calculated the Young's modulus of each single crystal phase in the coating to illustrate the difference in plastic deformation of the aluminum-zinc-silicon-magnesium coating after deformation and stress.

[0034] The elastic modulus of a single crystal is E, S 11 , S 33 , S 13 , S 44 is the compliance coefficient acting in different crystallographic directions, θ is the angle between a certain crystal plane (hkil) of the calculated HCP metal and the (0001) plane, then E and the flexibility coefficient have the following relationship:

[0035] 1 / E=S 11 (sin 4 θ)+S 33 (cos 4 θ)+(2S 13 +S 44 )(cos 2 θ)(sin 2 θ) (1)

[0037] The crystal plane angle is calculated by the following formula:

[0038] cosθ=0.75×(a / c) 2 ×l×{0.75(a / c) 2 ×(h 2 +k 2 +hk+0.75(a / c) 2 × 2 )}^(-1 / 2)(2)

[0040] The anisotropy coefficient is calculated by the following formula:

[0041] f E =S 11 / S 33 (3)

[0042] For cubic single crystals, the following relationship holds:

[0043] 1 / E=S 11 -2(S 11 -S 12 -1 / 2×S 44 )(L1^2×L2^2+L2^2×L3^2+L3^2×L1^2) (4)

[0045] Crystal plane angle:

[0046] cosθ=(h1h2+k1k2+l1l2) / {(h1 2 +k1 2 +l1 2 ) (1 / 2) ×(h2 2 +k2 2 +l2 2 ) (1 / 2)} (5)

[0048] Anisotropy coefficient:

[0049] f E =(2C44 +C 12 ) / C 11

[0050] The calculated elastic modulus and anisotropy coefficient of each single crystal phase of the close-packed hexagonal structure and body-centered cubic structure are shown in Table 1.

[0051] Table 1 Young's modulus (GPa) and anisotropy coefficient of low-index crystal planes of HCP and FCC structure single crystals in Al-Zn-Si-Mg coatings

[0052]

[0053] It can be seen from the calculation results in Table 1 that the elastic moduli of MgZn2, Mg2Si phase, Si phase and aluminum-rich dendrite phase in the coating are greatly different. Therefore, when the alloy coating is bent and deformed, the coating is easily cracked due to the plasticity difference between the aluminum dendrites and the alloy phase between the dendrites.

[0054] In order to solve the above problems and based on the premise of not affecting the corrosion resistance of the alloy coating, the size or distribution of the alloy phase between the aluminum dendrites in the alloy coating should be strictly controlled. Therefore, when the coating structure contains both Mg-Zn phase and Mg-Si phase, the size of the irregular block-shaped Mg-Zn phase between the dendrites in the cross-sectional structure of the coating should be no more than 3 μm, and a certain amount of Mg-Si phase is formed to replace the single Si phase to reduce the difference in deformability between the Mg-Si phase and the aluminum-rich phase, and to ensure that a certain amount of magnesium-containing alloy phase provides Mg in the corrosive medium. 2+ Ions improve the corrosion resistance of the coating.

[0055] Furthermore, the size of the zinc-rich phase in the cross-sectional microstructure of the coating, which is distributed in granular or irregular blocks between dendrites, should be no greater than 2 μm. From the above calculation results, it can be seen that the elastic anisotropy of the zinc-rich phase in the coating is the largest, and the coating is very likely to undergo crack expansion in the zinc-rich phase during bending. However, since the zinc-rich phase is generated at the end of solidification, it is generally located inside the eutectic phase and is beneficial to improving the corrosion resistance of the coating. When the size of the zinc-rich phase in the coating is higher than the range required by the present invention, it indicates that a large degree of component segregation occurs in the coating during solidification, which is not conducive to the refinement of the coating structure and will reduce the content of the ternary alloy phase in the coating, significantly reducing the corrosion resistance of the coating.

[0056] Furthermore, in the immersion plating process of the alloy coating described in the present invention, due to the high aluminum content in the plating solution, it is necessary to add more than 1% of silicon to inhibit the violent reaction between the plating solution and the iron element, so as to ensure the bonding force between the coating and the steel base. After participating in the reaction between the iron base and the plating solution to form an alloy layer, the remaining silicon element will react with the magnesium element to form a Mg-Si phase between the aluminum-rich dendrites in the middle of solidification. Limited by the magnesium content, a certain amount of single silicon phase is usually generated. It can be seen from the calculated value of the elastic modulus that the elastic modulus of the single silicon phase is the largest, that is, the plasticity is the worst. When the single silicon phase is arbitrarily distributed in the coating, it is very unfavorable for the bending performance and corrosion resistance of the alloy coating described in the present application. Therefore, the distance between the single Si phase distributed between the dendrites in the cross-sectional organizational structure of the coating and the inhibition layer between the coating and the substrate in the direction perpendicular to the coating thickness is not greater than 1 / 3 of the total coating thickness, and the mass content of the single Si phase accounts for a proportion of the interdendritic phase of not more than 1%, which can effectively inhibit the initiation and propagation of cracks caused by the distribution of silicon elements when the coating is bent and deformed.

[0057] The inventors also found that when the alloy coating is bent and deformed, the bending stress on the outer surface of the coating increases with the thickness of the coating, and the uniformity of the coating thickness will seriously affect the cracking behavior of the coating during bending. Therefore, in the cross-sectional organizational structure of the coating described in the present application, the coating thickness deviation measured from the inhibition layer between the coating and the substrate to the coating surface within a 50μm length randomly selected in the horizontal direction should not be greater than 10%, so as to ensure the uniformity of the coating thickness.

[0058] In addition, in order to control the uniformity of cracks generated in the alloy coating described in the present application during the bending process, so that the alloy coating can obtain a color coated steel plate with high surface quality in the subsequent painting or continuous coating process, the microstructure of the alloy coating should be refined as much as possible. The more layers of the cross-sectional microstructure of the coating, the higher the degree of refinement of the coating microstructure. Therefore, the coating structure divided by aluminum dendrite alloy phases or tissues in the cross-sectional microstructure of the coating perpendicular to the coating thickness direction should be no less than 3 layers.

[0059] The magnesium content in the alloy coating is set to 1.5% to 2.5%: the improvement of the excellent bending performance of the aluminum-zinc-silicon-magnesium coating should be based on the premise of not losing the corrosion resistance. The coating contains a certain amount of Mg element to ensure that a certain amount of ternary eutectic phase and magnesium-zinc phase are generated in the coating. During the corrosion process of the coating, the magnesium-zinc phase and eutectic phase containing magnesium elements are prone to selective dissolution, generating high-density corrosion products covering the surface of the coating, inhibiting further corrosion of the coating in the corrosive medium, thereby significantly improving the corrosion resistance of the aluminum-zinc-silicon-magnesium coating. At the same time, when the Mg content is maintained between 2.0% and 2.5%, the strong affinity between magnesium and silicon elements can generate magnesium-silicon phases in the coating, which can effectively reduce the content of free silicon in the coating. The coating can also provide a certain amount of magnesium ion dissolution during the corrosion process to ensure the high corrosion resistance of the coating. However, too high a magnesium content will make it difficult to control the oxidation of the coating surface and deteriorate the surface quality of the coating. Therefore, the magnesium content is controlled within the reasonable range described in this application.

[0060] Adding trace amounts of Ti elements to the coating: After adding titanium elements, the Ti-Al phase generated has a lower lattice mismatch with the aluminum-rich phase, which promotes the nucleation of the aluminum-rich phase on the Ti-Al alloy phase particles. In addition, trace amounts of titanium elements can have a strong growth inhibition effect on the growth of aluminum dendrites, inhibiting the growth of aluminum-rich dendrites after nucleation. Therefore, trace amounts of titanium elements in aluminum-zinc-silicon-magnesium coatings have a significant effect on the refinement of aluminum dendrites during the solidification process of the coating. Excessive titanium elements are prone to generate excessive high-melting-point Ti-Al phases in the alloy plating solution, and the amount of slag in the zinc pot increases, which is not conducive to industrial production and the control of coating surface quality.

[0061] Add 0.04% to 0.06% of lanthanum-cerium mixed rare earth elements in the coating: rare earth elements have a strong purification effect on the alloy plating solution; as a surfactant, they can reduce the wetting angle between the nucleation substrate and the aluminum-rich phase, and refine the Al grains; at the same time, trace amounts of mixed rare earth elements have a strong metamorphic effect on the first precipitated Si phase, which can significantly change the morphology and distribution of the Si phase in the coating, which is beneficial to the improvement of the bending performance of the coating. The effect of trace rare earth elements is very significant, and too high a content is not conducive to the balance of the zinc pot slag system. Moreover, due to the low recovery rate of rare earth elements, too high a rare earth content is not conducive to reducing production costs.

[0062] The content of Zn in the coating is controlled at 45% to 50%: Due to the mutual solubility of aluminum and zinc, appropriately increasing the content of zinc in the coating can produce a strong solid solution strengthening effect, improve the strength of the aluminum-rich phase, enhance the coordinated deformation ability of the aluminum-rich phase and the aluminum dendrite interphase during the bending process of the coating, and improve the bending performance of the coating; the liquid phase with a higher zinc content has a stronger wettability to the aluminum-rich phase in the later stage of solidification, which can strengthen the bonding force between the zinc-rich alloy phase and the ternary phase and the aluminum-rich phase, strengthen the interface bonding force during deformation, and improve the ability to resist cracks during bending.

[0063] The coating cooling process control requirements of the present invention include: the front-stage fan is used to cool the strip to 440°C after the air knife, and the cooling rate is controlled at 8°C / s to 15°C / s; when the strip temperature is between 390°C≤440°C, the middle-stage fan is used for cooling, and the cooling rate is controlled at 15 to 20°C / s; when the strip temperature is between 280°C≤390°C, the rear-stage fan is used for cooling, and the cooling rate is controlled at 25 to 35°C / s. The front-stage cooling refines the aluminum-rich dendrites while ensuring that the cooling rate is not too large; the middle-stage cooling uses a higher cooling rate to suppress the size and content of the magnesium-zinc phase and the magnesium-zinc phase during the solidification process of the coating, which is beneficial to the improvement of the bending performance of the coating; the rear-stage cooling uses the highest cooling rate to suppress the further eutectoid reaction of the aluminum-rich phase in the coating, avoiding the generation of large-sized zinc-rich phases and aluminum-rich phases.

[0064] The zinc pot temperature and cooling device nozzle of the present invention: accurate zinc pot temperature control is beneficial to reducing the amount of slag in the pot, and the use of a "straight seam" type air outlet nozzle can make the coating surface cool more evenly, can effectively suppress surface defects caused by uneven local cooling, and is beneficial to the production of products with high surface quality.

[0065] The present invention will be described in detail below with reference to embodiments, comparative examples and experimental data.

[0066] Example 1-Example 2, Comparative Example 1-Comparative Example 2

[0067] A method for manufacturing an aluminum-zinc-silicon-magnesium coated steel plate with excellent bending performance, comprising hot-dip plating on a substrate; using a cold-rolled plate as the substrate, the steel plate material used for the substrate is CQ grade, and includes the following components in mass percentage: C: 0.02%, Si: 0.03%, Mn: 0.2%, P: 0.015%, S: 0.008%, and the balance is Fe and inevitable impurities. The chemical composition of the plating solution is shown in Table 2, and the balance is Al and inevitable impurity elements and the content is less than 1%.

[0068] The immersion plating control requirements include: the front-stage fan is used to cool the strip to 440°C after the air knife exits, and the cooling rate is controlled at 8°C / s to 15°C / s; when the strip temperature is between 390°C ≤ and <440°C, the middle-stage fan is used for cooling, and the cooling rate is controlled at 15 to 20°C / s; when the strip temperature is between 280°C ≤ and <390°C, the rear-stage fan is used for cooling, and the cooling rate is controlled at 25 to 35°C / s.

[0069] During the immersion plating process, the zinc pot temperature is 590-600°C, the zinc pot temperature deviation is ±1°C, the strip air outlet knife temperature is 5-10°C lower than the pot temperature, and the cooling device nozzle type is a "straight seam" type.

[0070] The weight of aluminum-zinc-silicon-magnesium coating after immersion plating is 150g / m 2 ~200g / m2 .

[0071] Comparative Example 1-Comparative Example 2

[0072] A method for manufacturing an aluminum-zinc-silicon-magnesium coated steel plate comprises hot-dip plating on a substrate; the substrate steel plate material is CQ grade, and the substrate comprises the following components in mass ratio: C: 0.02%, Si: 0.03%, Mn: 0.2%, P: 0.015%, S: 0.008%, and the balance is Fe and unavoidable impurities. A plating solution of comparative example 1-2 is prepared, and the chemical composition of the plating solution is shown in Table 2, and the balance is Al and unavoidable impurity elements and the content is less than 1%.

[0073] Examples 1-2 and Comparative Examples 1-2 were produced using the same process. The different preparation process parameters are shown in Table 3. The coating phase composition and coating bending properties are shown in Tables 4 and 5.

[0074] Table 2 Plating solution composition and coating weight of examples and comparative examples

[0075]

[0076] Table 3 Main process parameters for preparing various embodiments and comparative examples

[0077]

[0078]

[0079] The coating structure and bending performance of the aluminum-zinc-silicon-magnesium coated steel sheets prepared according to the plating solution composition and process parameters in the above-mentioned embodiments and comparative examples and the preparation method of the present invention were tested and analyzed, and the evaluation methods used were as follows: (1) The coated steel sheets in the embodiments and comparative examples were subjected to 0T to 4T bending tests according to the bending test provisions in "GB T 13448-2019 Test Methods for Color Coated Steel Sheets and Steel Strips"; (2) After T-bending, 3M transparent tape was used to adhere to the surface of the coated layer after bending, and then the tape was quickly opened to observe whether the metal coating peeled off on the tape; (3) The crack width was observed and measured under the same magnification of an electron microscope; (4) The distribution and size of the characteristic phases in the coating structure were analyzed using ImigeJ image processing software; (5) A neutral salt spray test was carried out according to ASTM B117, the sample size was 75 mm × 150 mm, the edge of the sample was sealed with 3M tape, and the sample was placed in a neutral salt spray test box for 1500 to observe whether there was red rust on the surface of the sample. The test evaluation results are shown in Tables 4 and 5.

[0080] Table 4 Coating cross-sectional structure characteristics and coating thickness of the embodiments and comparative examples

[0081]

[0082] Table 5 Test results of bending performance and corrosion resistance of coatings in Examples and Comparative Examples

[0083]

[0084]

[0085] From the evaluation results in Table 5 and Figure 3-Figure 4 , Figure 5-Figure 6 , Figure 7-Figure 8 It can be seen that compared with comparative examples 1-2, the coating structure of the galvanized aluminum-magnesium coated steel plate prepared in Examples 1 and 2 of the present invention has a smaller crack width after 0T, 2T, and 4T bending deformation, and the crack uniformity is good. The coating in the embodiment presents a more obvious layered morphology, indicating that the coating structure refinement effect is obvious. In addition, the magnesium-silicon phase content in the coating is higher than that in the comparative example, while the silicon phase content and the size of the zinc-rich phase and the magnesium-zinc phase are lower than those in the comparative example. The surface coating has better crack propagation resistance and the coating has better bending performance. According to the comparison of the surface dendrite morphology, it can be seen that the size of the aluminum flower on the surface of the coating of the embodiment is smaller than that of the comparative example, which inhibits the extension and expansion behavior of the cracks in the coating and reduces the proportion of long cracks after the coating is bent and deformed. No red rust is produced on the surface of the 1500h neutral salt spray test sample, and it has the same corrosion resistance.

[0086] The underlined data above do not meet the requirements of the present invention.

[0087] The description of the above embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the protection scope of the present invention.

Claims

1. An aluminum-zinc-silicon-magnesium coated steel plate with excellent bending performance, comprising a substrate, an inhibition layer and a coating; characterized in that: In the cross-sectional microstructure of the aluminum-zinc-silicon-magnesium coated steel plate with excellent bending performance, in the cross-sectional microstructure of the coating, the coating thickness deviation measured from the inhibition layer between the coating and the substrate to the coating surface within a 50 μm length randomly selected in the horizontal direction is no more than 10%.

2. The aluminum-zinc-silicon-magnesium coated steel sheet with excellent bending performance according to claim 1, characterized in that: The cross-sectional microstructure of the coating has at least three layers of coating structures divided by aluminum interdendritic alloy phases or eutectic structures in a direction perpendicular to the coating thickness.

3. The aluminum-zinc-silicon-magnesium coated steel sheet with excellent bending performance according to claim 1, characterized in that: The mass content of the Mg-Si phase contained between the dendrites in the cross-sectional organizational structure of the coating is more than 3 times the mass content of the silicon phase between the dendrites.

4. The aluminum-zinc-silicon-magnesium coated steel sheet with excellent bending performance according to claim 1, characterized in that: The distance between the single Si phase distributed between dendrites in the cross-sectional organizational structure of the coating and the inhibition layer between the coating and the substrate in the direction perpendicular to the coating thickness is no more than 1 / 3 of the total coating thickness, and the mass content of the single Si phase accounts for no more than 1% of the interdendritic phase.

5. The aluminum-zinc-silicon-magnesium coated steel sheet with excellent bending performance according to claim 1, characterized in that: In the cross-sectional organizational structure of the coating, the interdendritic regions contain Mg-Zn phases that are distributed irregularly in blocks and have a size of no more than 3 μm.

6. The aluminum-zinc-silicon-magnesium coated steel sheet with excellent bending performance according to claim 1, characterized in that: The zinc-rich phase between dendrites in the cross-sectional organizational structure of the coating is distributed in granular or irregular blocks and has a size of no more than 2 μm.

7. A method for manufacturing the aluminum-zinc-silicon-magnesium coated steel sheet with excellent bending performance according to any one of claims 1 to 6, characterized in that: The manufacturing method comprises immersion plating, and the used plating solution comprises the following components in mass percentage: Zn: 45% to 50%, Mg: 1.5% to 2.5%, Si: 1.0 to 1.5%, Ti: 0.002% to 0.005%, La+Ce content 0.04% to 0.06%, and the balance is Al and unavoidable impurity elements.

8. The manufacturing method according to claim 7, characterized in that: The immersion plating control is as follows: the front-stage fan is used to cool the strip to 440°C after the air knife exits, and the cooling rate is controlled at 8°C / s to 15°C / s; when the strip temperature is between 390°C ≤ and <440°C, the middle-stage fan is used for cooling, and the cooling rate is controlled at 15 to 20°C / s; when the strip temperature is between 280°C ≤ and <390°C, the rear-stage fan is used for cooling, and the cooling rate is controlled at 25 to 35°C / s.

9. The manufacturing method according to claim 7 or 8, characterized in that: During the immersion plating process, the zinc pot temperature is 590-600°C, the zinc pot temperature deviation is ±1°C, and the strip air outlet knife temperature is 5-10°C lower than the pot temperature.

10. The manufacturing method according to claim 7 or 8, characterized in that: The weight of aluminum-zinc-silicon-magnesium coating after immersion plating is 150g / m 2 ~200g / m 2 .

Citation Information

Patent Citations

  • Minimized spangle hot-dipped aluminum-zinc steel plate containing rare earth and production method thereof

    CN108504912A

  • Hot-dip coated steel plate with excellent corrosion resistance and method for manufacturing hot-dip coated steel plate

    CN109402547A

  • laminate

    CN109476121A

  • Method for eliminating zinc ripple defect of alloyed hot-dip galvanized steel sheet

    CN113430478A

  • Multilayer metal ball

    WO2018056315A1